El principio del interés superior del niño en la educación inicial y sus implicaciones pedagógicas y éticas en la práctica docente (Architecture Image Studies, 2026)
The principle of the best interests of the child constitutes a fundamental guideline in the protection of children’s rights and has direct implications for educational practice, particularly in early childhood education. This study aims to analyze the principle of the best interests of the child in Ecuadorian early childhood education and its pedagogical and ethical implications for teaching practice. A qualitative approach was adopted, using a descriptive–interpretive and exploratory design. Data were collected through semi-structured interviews with 20 early childhood teachers, non-participant classroom observations, and document analysis. The data were analyzed using inductive thematic analysis, allowing the identification of emerging categories related to teachers’ understandings, practices, and ethical dilemmas.The findings reveal that the principle of the best interests of the child is present in teaching practice mainly in an implicit manner, expressed through care-oriented actions and concern for children’s emotional well-being. However, its application is not always grounded in an explicit rights-based framework, generating tensions between institutional demands and pedagogical decisions. The study highlights the role of teachers as moral agents and direct guarantors of children’s rights and emphasizes the need to strengthen ethical and rights-based training in early childhood education. These findings contribute to the discussion on educational ethics and children’s rights by providing contextualized evidence from the Ecuadorian educational system.